State-of-the-art review on health monitoring of transmission line conductors - Saravanan, T. Jothi; Rao, N. Prasad; Gopalakrishnan, N. (Journal of Structural Engineering, 2025)
This paper presents a critical review of literature on Structural Health Monitoring (SHM) of Overhead Transmission Line (OVTL) conductors. Different health monitoring techniques such as wave propagation mechanics and other significant methodologies used for remaining life prediction is discussed in detail. From the critical review of monitoring techniques, it has been observedthat some of the methods have complex approach involving many parameters. In the present work, research papers on different topics e.g. study of wave propagation techniques, study on guided waves, damaged conductors are reviewed. Wave propagation analysis has been used extensively in Non-Destructive Testing (NDT) techniques. However, in the context of intelligent health monitoring tasks, there are several possibilities that such wave propagation analysis can be employed along with certain emphasis on efficient modelling and signal processing aspects. The widely used SHM technique based on guided wave approach have been explained. The main objective of this literature survey is to study the available techniques and to propose the required research work for the development of SHM of OVTL conductors using wave propagation techniques. Research in these areas is of paramount importance so that an automatic warning and alert system can be implemented.